Measuring the impact of European colonization on Native American populations in Southern Brazil and Uruguay: Evidence from mtDNA. Issue 3 (23rd April 2019) - Tavares, Gustavo M.; Reales, Guillermo; Bortolini, Maria Cátira; Fagundes, Nelson J. R.
Abstract: Objectives: The major aim of this article was to estimate the demographic impact of European arrival and colonization over Native American populations from southern Brazil and Uruguay. We also compared the mitochondrial DNA (mtDNA) genetic diversity, structure, and demography of Native American lineages present in current indigenous (Natives) and nonindigenous admixed (Admixed) populations to estimate the effective population size ( N e ) of contemporary and ancestral (pre‐Columbian) Native American populations. Methods: We retrieved published mtDNA sequences from Native (n = 396) and Admixed (n = 309) populations from southern Brazil, Uruguay, and surrounding areas. We conducted genetic diversity, structure, and demographic analyses. Finally, we used Approximate Bayesian Computation to estimate the N e for current Native, Admixed, and pre‐Columbian Native American populations. Results: We found higher Native American mtDNA genetic diversity in admixed rather than in indigenous populations (131/309 vs 27/396 different haplotypes, respectively). Only Admixed populations maintained ancient signals of the Native American population expansion approximately 14 to 17 kya, which have decayed in Natives. Our N e estimates suggest that Natives represent only 0.33% (0.18%‐1.19%) of the N e for ancestral pre‐Columbian indigenous populations. Conclusions: Admixed populations represent an important genetic reservoir of Native American lineages, many of which are extinct in contemporary indigenous populations. In addition, the Native American lineages present in Admixed populations retain part of the past demographic history of Native Americans. The intensity of the reduction is congruent with historical accounts of strong indigenous depopulation during the colonization process.